Doença e estigma - Monteiro, Yara Nogueira (Revista de História, 1993)
The history of leprosy is profoundly interrelated with the medieval heritage of stigmatization and prejudice. This article intends to demonstrate how this process ocurred and continues to penetrate into the collective imaginary about the disease. Through a comparison between leprosy and tuberculosis as well as how both are treated by literature, this article points out the strength of the imaginary over the real and how the stigmatization has been able to resist the scientific advancement and the discovery of a cure to the disease.